IMPROVEMENT OF METHODOLOGICAL AND PRACTICAL BASIS FOR ENSURING THE COMPETITIVENESS OF COMMERCIAL BANKS (American Journal of Business Management, Economics and Banking, 2025)
Ensuring the competitiveness of commercial banks is mandatory a condition for increasing their role as a financial intermediary in the development of the national economy. Therefore, leading research centers and prestigious higher education institutions conduct research on increasing the level of capitalization of commercial banks, ensuring a stable level of net profit for banks in relation to assets weighted by risk, achieving a quantitative balance between the assets and liabilities of commercial banks, ensuring the sufficiency of the deposit base of banks, increasing the profitability of assets of commercial banks, improving the practice of assessing and managing risks associated with active operations of banks, ensuring the competitiveness of banking products based on innovations. This indicates the relevance of the issue of ensuring the competitiveness of commercial banks.The article analyzes the current state of competitiveness of commercial banks in Uzbekistan and develops scientific proposals aimed at improving the methodological and practical foundations for ensuring the competitiveness of commercial banks in the republic.